Selecting the Location of a Nautical Tourism Port by Applying PROMETHEE And GAIA Methods Case Study – Croatian Northern Adriatic - Kovačić, Mirjana (Promet - Traffic&Transportation, 2012)
In this paper, the author presents the multi-criteria analysis methods, PROMETHEE I and II and GAIA, used for selecting the location of a nautical tourism port. In an example of the selected location of a nautical tourism port in the Northern Adriatic, the author has used an analytic and graphical evaluation for solving such a problem. Particular attention has been paid to the use of GAIA method, which is suitable for visualisation of the problem characteristics through geometrical interpretation and presentation of the results of a multi-criteria analysis. By application of the described methods, it is possible to establish the most acceptable location considering the principles of sustainable development. The paper emphasises the importance of applying multi-criteria analysis and multi-criteria use of selected methods, which contain criteria and sub-criteria for selecting the optimal location of a nautical tourism port. In the paper the results of the research “Criteria for selecting the location of a nautical tourism port” conducted during 2006/2007 have been used. KEY WORDS: nautical tourism port, selecting the location, multi-criteria analysis